1993
DOI: 10.1007/bf02426356
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum CA125 levels in early intrauterine and tubal pregnancies

Abstract: Using an immunoradiometric assay, serum CA125 levels were measured in 13 women with a normal pregnancy, 9 with a spontaneous abortion, 3 with a hydatidiform mole, and 15 with a tubal pregnancy. Serum CA125 levels were high in patients with a normal pregnancy (154 +/- 169 U/ml; mean +/- S.D.), a spontaneous abortion (244 +/- 258 U/ml), or a hydatidiform mole (54 +/- 16 U/ml). In contrast, CA125 levels in patients with a tubal pregnancy (33 +/- 25 U/ml) were low, and almost all of those without uterine bleeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…The results of our study are similar to the results of many studies in terms of the high level of CA‐125 in early intrauterine pregnancy 6–10 . Nevertheless, our findings, with regards to the CA‐125 levels in ectopic pregnancy, have shown partial contradiction, 3–6 or resemblence 4,5 , 10 with the findings of published studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of our study are similar to the results of many studies in terms of the high level of CA‐125 in early intrauterine pregnancy 6–10 . Nevertheless, our findings, with regards to the CA‐125 levels in ectopic pregnancy, have shown partial contradiction, 3–6 or resemblence 4,5 , 10 with the findings of published studies.…”
Section: Discussionsupporting
confidence: 91%
“…Kobayashi et al . found that serum CA‐125 levels are high in women with normal early pregnancy, spontaneous abortion, and hydatiform mole, but they are low in women with tubal pregnancy, especially if there has been no uterine bleeding 10 . They reported that a transient elevation of the CA‐125 levels occur in maternal serum in early pregnancy and just after delivery, and they thought that destruction of the decidual tissues may cause this transient elevation of CA‐125 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In women of childbearing age there are changes in serum CA-125 during the menstrual cycle. Small increases, less than 2-fold, are found during menstruation [12] and in normal pregnancy [13]. Both pericardial effusions [14] and Pleural effusions [15] have been found to be associated with increases in serum CA-125.…”
Section: Resultsmentioning
confidence: 97%
“…In spite of that, CA-125 is widely used as a second line investigation (Aslam et al 2000). Serum CA-125 is reported to be particularly high during the first trimester and this is largely attributed to increased production by the deciduas (Jacobs et al 1988), and then is said to decline with increasing gestation, indicating that a higher cut-off value should be used in pregnant women as compared with non-pregnant women (Kobayashi et al 1993; Bon et al (Knudsen et al 2004) and therefore it should be approached with caution. In a study conducted on 188 women with uncomplicated pregnancies and sonographically normal ovaries between 11 and 14 weeks' gestation, serum CA-125 were found to be raised, and thus it was concluded that cut-off values of CA-125, which are usually used to assess the nature of ovarian cysts in non-pregnant women, cannot be applied to pregnant women (Aslam et al 2000).…”
Section: Role Of Ca-125mentioning
confidence: 91%